School Well-Being pada Siswa Berprestasi Sekolah Dasar yang Melaksanakan Program Penguatan Pendidikan Karakter - Faizah Faizah; Jovita Nabila Prinanda; Ulifa Rahma; Yuliezar Perwira Dara (Psympathic : Jurnal Ilmiah Psikologi, 2018)
The aim of this study was to evaluate school well-being of achieving students in primary school that implement character education programs. This research used qualitative method, data was collected by using interview and observation with 2 primary subjects achieving student on academic or non academic skill, and 5 secondary subjects were teacher, parent, peer of primary subjects. Data was analyzed by Analysis Interactive Model with triangulation source validity. School well-being consists of four dimensions: having, loving, being, and health. The result of this study describes school well-being of achieving student in primary school with character education program.